This I Believe - Wilkes, Frank M. (Tufts Archival Research Center, 2006)
Frank Wilkes remembers his mother and the beliefs she imparted to him, such as the dignity of work, the omnipotence of God, and the need to follow God's commandments and leave the consequences to Him.